Growth of leaf cutting of orange lemon (Citrus limon L. Osbeck) with red onion extract treatment - Fatonah, Siti; Sasa Royanti (Jurnal Pertanian, 2023)
Cultivation of lemons needs to be increased due to the increasing demand for lemons. This requires a large amount of seedling. One alternative material for cuttings for lemongrass nurseries with lots of supplies is leaf cuttings. The aims of this study were to determine the effect of onion extract concentration on the growth of leaf cuttings and to determine the best concentration of shallot extract on the growth of leaf cuttings. The experimental research was in the form of extract treatment, which consisted of 5 levels, namely control (without immersion), immersion in water, 10% onion extract, 20% onion extract and 30% shallot extract. Leaf cuttings were soaked in onion extract at various concentrations for 2 hours. The observed variables included the percentage of living cuttings, the percentage of roots formed, the number of roots, the length of the roots, the percentage of damaged leaves, the percentage of shoots formed and the length of shoots. All treatments showed 100% survival rate and root formation percentage. Treatment of 20% onion extract can increase the number of roots, root length, percentage of shoots formed and shoot length from lemon lime leaf cuttings at 60 days after observation. The results of this study provide information that cuttings from leaves can be used as an alternative in the vegetative propagation of lemon and onion extracts as an alternative to growth regulators.